Analysis of the influence of the moment the internationalization process begins on the internationalization intensity of family and nonfamily businesses: An approach using a Tobit model - Oscar Javier Varas-Fuente; Raquel Arguedas-Sanz; Beatriz Rodrigo-Moya (Administrative Sciences, 2022)
The specific characteristics of family businesses as well as the internationalization path followed can influence the intensity of the internationalization process. Many studies have analyzed how family character can influence the internationalization process of family businesses, and the results obtained have not been conclusive. Nevertheless, previous research has not sufficiently addressed the influence that the moment of initiation of the internationalization process has on the levels of internationalization achieved. Based on the behavioral agency model, the unique set of business resources (familiness), and the socioemotional wealth (SEW) perspective, this study examines, the internationalization intensity of family and nonfamily businesses in two defined groups (early internationalization and internationalization from the local market). Likewise, the effect that the entry of the second generation has on the internationalization of these companies is analyzed. To perform this analysis, Tobit regression models are estimated from a data set of panel data from the Spanish Survey on Business Strategies for small and medium-sized Spanish family businesses from 2005 to 2016, finding that family ownership and management have a negative influence on the intensity of exports, regardless of the path of internationalization followed, and that the entry of new generations has a positive relationship with the level of internationalization of these businesses. Finally, implications of the findings for research and management are discussed.
Keywords: 350; behavioral agency model; family businesses; internationalization paths; mixed gamble; SEW; Tobit model